Work-family conflict and turnover intention: Mediation model for millennial government employees - Erni Masdupi; Risang Kurniawan Prasojo; Mely Oktia Darni (Problems and Perspectives in Management, 2023)
Every organization is not only faced with the challenge of recruiting employees but also of retaining talent within the organization. This study analyzes the influence of work-family conflict on millennial government employees’ turnover intention and determines how job embeddedness and job stress can be a mediator in this case. This paper used a questionnaire to accumulate data from 419 millennial employees in the government sector in Indonesia. SEM-PLS was used to test the influence of inter-variable relations. The results of SEM tests via Smart-PLS 3 software reveal that work-family conflict has a positive and significant influence on turnover intention. Job embeddedness and stress can mediate work-family conflict on turnover intentions of millennial employees in the government sector. Furthermore, work-family conflict has a negative and significant influence on job embeddedness and a positive and significant influence on job stress. Next, job embeddedness has a negative and significant influence on turnover intentions, and job stress has a positive and significant influence on such intentions. Therefore, the Indonesian government must reduce time stress and increase the job embeddedness employees, reducing turnover intentions. In addition, the Indonesian government needs to develop a policy supporting employee work-life balance. AcknowledgmentThis study is funded by Lembaga Penelitian dan Pengabdian Masyarakat Universitas Negeri Padang. The Human Resources Management and Behavioural Research Group Faculty of Economy and Bussiness, Universitas Negeri Padang also supported this paper.